Constitutional Question (Antara Realitas Politik dan Implementasi Hukumnya) - Jazim Hamidi; Mustafa Lutfi (The Constitutional Court of the Republic of Indonesia, 2016)
The emergence of political and constitutional law discourses, side by side with the growth of democracy in Indonesia, is developing progressively and dynamically. In reality, this nation is under great tests which determine whether the state is still holding its constitutional commitment on upholding the rule of law. In the other side, the face of law enforcement in this state is under an immense storm of urgent issues that need immediate solution which is: can this state provide “justice” unto all of its citizens? This issue is a huge homework for all the nation’s elements in the future.The establishment of the Constitutional Court which regulated in the 1945 Constitution surely related to the constitutional reformation which deemed as a necessity and an important agenda that should be applied fundamentally. The existence of the Constitutional Court in the constitutional system of the Republic of Indonesia simultaneously casting new hopes for any justice-seekers. The surfacing question now is will the Constitutional Court capable in faithfully guarding the democracy and fair constitutionality in the verge of society that has already loose confidence towards justice institution? This simple and short writing attempts to study and discuss on constitutional question, including on how its political reality and its legal implementation in Indonesia, and also a slight hope of this writing in enriching the references for any justice-lovers in this nation.